2006
DOI: 10.1074/jbc.m601823200
|View full text |Cite
|
Sign up to set email alerts
|

Transformation by the Rho-specific Guanine Nucleotide Exchange Factor Dbs Requires ROCK I-mediated Phosphorylation of Myosin Light Chain

Abstract: Dbs was identified in a cDNA-based expression screen for sequences that can cause malignant growth when expressed in murine fibroblasts. In previous studies we have shown that Dbs is a Rho-specific guanine nucleotide exchange factor that can activate RhoA and/or Cdc42 in a cell-specific manner. In this current study we have used a combination of genetic and pharmacological approaches to examine the relative contributions of RhoA⅐PRK and RhoA⅐ROCK signaling to Dbs transformation. Our analysis indicates that ROC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Our previous studies have shown that onco-Dbs mediates transformation in fibroblasts through regulation of MLC2 in a RhoA/ROCK-dependent manner (37). Consistent with this, onco-Dbs activates RhoA when overexpressed in T47D cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Our previous studies have shown that onco-Dbs mediates transformation in fibroblasts through regulation of MLC2 in a RhoA/ROCK-dependent manner (37). Consistent with this, onco-Dbs activates RhoA when overexpressed in T47D cells.…”
Section: Discussionsupporting
confidence: 53%
“…Immunoprecipitation and Western Blot Analysis-Immunoprecipitation and Western blot analysis were performed as previously described (37). Antibodies used for Western blots Statistics-Statistical analyses were performed by one-way analysis of variance followed by the Tukey HSD (honestly significant difference) test for multiple comparisons using JMP statistical software.…”
Section: Methodsmentioning
confidence: 99%
“…ACACA , RARA , NOTCH1 and NUP214 are known to form translocations in various types of hematological malignancies while many other fusion genes involve suspected oncogenes, such as RPS6KB1 ( RPS6KB1-TMEM49 and RPS6KB1-SNF8 ) [25], GSDMB ( TATDN1-GSDMB ) [26] and MCF2L ( LAMP1-MCF2L ) [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Construction of pAX142-IκB(SS), pAX142-H-ras-61L, pAX142-bcr(491-876) and pAX142-Tsg101 have been described previously [22,23]. pCAG-rock(KD) which encodes the kinase-defective version of ROCK I and pCAG-rock(WT) constructs were provided by S. Narumiya [24]. The reporter constructs utilized in the luciferase-coupled transcriptional assays, have been described previously [22,25].…”
Section: Molecular Constructsmentioning
confidence: 99%